Nephroprotective effect of melatonin and L-Ascorbic acid (Vitamin-C) against ampicillin- induced toxicity in Funambulus pennanti. Issue 1 (1st January 2020) - Rastogi, Shraddha; Gupta, Sameer; Haldar, Chandana; Chandra, Dinesh
ABSTRACT: Ampicillin is one of the most commonly prescribed antibiotics against intra-renal infections. Prolonged use of ampicillin has been found to be associated with a high rate of free-radical generation and oxidative stress induced nephrotoxicity. In the present study, we report the comparative effects of melatonin and vitamin-C (Vit-C) in ameliorating the biochemical and structural alterations in renal tissues caused by ampicillin sodium. Biochemical parameters such as acid phosphatase (ACP), alkaline phosphatase (ALP), creatinine and urea levels in urine and serum as well as oxidative stress parameters such as superoxide dismutase (SOD) activity, catalase activity, total antioxidant status (TAS%) and lipid peroxidation in the renal cortical tissues were accessed upon treatment of melatonin and Vit-C following ampicillin sodium administration in F unambulus pennanti . Ampicillin treatment increased ACP, ALP, creatinine and urea levels in serum and urine, indicating renal damage. It also induced oxidative stress by increasing lipid peroxidation and decreasing the activity of antioxidative enzymes. However, the exogenous melatonin or Vit-C treatment inhibited ampicillin mediated renal damages. Melatonin or Vit-C pre-treatment significantly decreased ACP, ALP, creatinine, urea, TBARS level and increased SOD, catalase activity and TAS%. Our results suggest that the antibiotic induced nephrotoxicity can be ameliorated by melatonin or Vit-C via reduction of oxidative stress in renal tissues.